Transcriptomic Analysis Reveal the Molecular Mechanisms of Wheat Higher-Temperature Seedling-Plant Resistance to Puccinia striiformis f. sp. tritici - Tao, Fei; Wang, Junjuan; Guo, Zhongfeng; Hu, Jingjing; Xu, Xiangming; Yang, Jiarong; Chen, Xianming; Hu, Xiaoping (Frontiers in Plant Science, 2018)
Stripe rust, caused by Puccinia striiformis f. sp. tritici (Pst), is a destructive disease of wheat worldwide. The disease is preferably controlled by growing resistant cultivars. Wheat cultivar Xiaoyan 6 (XY 6) has been resistant to stripe rust since its release. In the previous studies, XY 6 was found to have higher-temperature seedling-plant (HTSP) resistance. However, the molecular mechanisms of HTSP resistance were not clear. To identify differentially expressed genes (DEGs) involved in HTSP resistance, we sequenced 30 cDNA libraries constructed from XY 6 seedlings exposed to several temperature treatments. Compared to the constant normal (15°C) and higher (20°C) temperature treatments, 1395 DEGs were identified in seedlings exposed to 20°C for 24 h (to activate HTSP resistance) and then kept at 15°C. These DEGs were located on all 21 chromosomes, with 29.2% on A, 41.1% on B and 29.7% on D genomes, by mapping to the Chinese Spring wheat genome. The 1395 DEGs were enriched in ribosome, plant-pathogen interaction and glycerolipid metabolism pathways, and some of them were identified as hub proteins (phosphatase 2C10), resistance protein homologues, WRKY transcription factors and protein kinases. The majority of these genes were up-regulated in HTSP resistance. Based on the differential expression, we found that phosphatase 2C10 and LRR receptor-like serine/threonine protein kinases are particularly interesting as they may be important for HTSP resistance through interacting with different resistance proteins, leading to a hypersensitive response.